Penguatan Karakter Bernalar Kritis Berbasis Integratif Moral untuk Siswa Sekolah Dasar dalam Program Kampus Mengajar di Indonesia - Nursalam Nursalam; Suardi Suardi (Graduate School of Universitas Negeri Malang, 2022)
The purpose of this study is to develop a model for enhancing elementary school students' critical reasoning character education based on moral integration in Indonesian teaching campus activities. This study employs a variety of research techniques, including questionnaires, observations, interviews, and documentation, which are then examined qualitatively and quantitatively. The results of the study indicate that strengthening the character of critical reasoning based on moral integrative and social collaboration is in the very frequent category at all stages of moral knowing, feeling, sinverbal, action, habitus, and culture from various campus teaching activities such as giving assignments, giving directions, collaborative thinking, and performing tasks based on their abilities, which are integrated into school activities involving all parties. Tujuan penelitian menghasilkan model penguatan pendidikan karakter bernalar kritis berbasis integrasi moral kepada siswa sekolah dasar dalam kegiatan kampus mengajar di Indonesia. Penelitian ini menggunakan metode penelitian campuran (mixed methods), menggunakan angket, observasi, wawancara dan dokumentasi, kemudian dianalisis secara kualitatif dan kuantitatif. Hasil Penelitian menunjukkan penguatan karakter bernalar kritis berbasis integratif moral dan kolaborasi sosial berada pada kategori sangat sering pada semua tahapan moral knowing, feeling, sinverbal, action, habitus dan culture dari berbagai kegiatan kampus mengajar seperti kegiatan pemberian tugas, pemberian arahan, berpikir bersama, dan mengerjakan tugas sesuai kemampuan, yang terintegrasi dalam kegiatan sekolah yang melibatkan semua pihak.